Raman microspectroscopy for probing the impact of a dietary antioxidant on human breast cancer cells - Medeiros, P. S. C. (2016)
Breast cancer is the second most common type of cancer worldwide and the most frequent among women, being the fifth cause of death from neoplastic disease. Since this is an oxidative-stress related neoplasia, it is largely preventable. A dietary isoflavone abundant in soybean - daidzein - is currently being investigated owing to its chemopreventive and/or chemotherapeutic properties towards the human MDA-MB-231 (metastatic, estrogen-unresponsive) and MCF-7 (estrogen-responsive) breast cancer cell lines. Biological assays for evaluation of antitumour and anti-invasive activities were combined with state-of-the-art vibrational microspectroscopy techniques. At 50 and 100 μM concentrations and 48 h incubation time, daidzein was found to induce a marked decrease in cell viability (ca. 50%) for MDA-MB-231 and MCF-7 cells (respectively ca. 50% and 42%) and 40% inhibition of cell migration. MicroRaman analysis of fixed cells upon exposure to this isoflavone unveiled its metabolic impact on both cell lines. Multivariate data analysis (unsupervised PCA) led to a clear discrimination between the control and DAID-exposed cells, with distinctive effects on their biochemical profile, particularly regarding DNA, lipids and protein components, in a cell-dependent way. This is the first reported study on the impact of dietary antioxidants on cancer cells by microRaman techniques.